Point-of-care and visual detection of Salmonella spp. and Cronobacter spp. by multiplex loop-mediated isothermal amplification label-based lateral flow dipstick in powdered infant formula. (July 2021) - Yang, Xinyan; Jiang, Yujun; Song, Yang; Qin, Xue; Ren, Yuwei; Zhao, Yueming; Man, Chaoxin; Zhang, Wei
Abstract: In this study, the invasion protein gene for Salmonella spp. and the 16S–23S rRNA internal transcribed spacer sequence for Cronobacter spp. were used as two species-specific targets simultaneously amplified using labelled primers in the multiplex loop-mediated isothermal amplification (mLAMP) reaction. Subsequently, the modified amplification products were monitored by lateral flow dipstick (LFD) through dual immunoreactions. The accumulation of gold nanoparticles produced characteristic red bands on the LFD, enabling simultaneous visual inspection. Under optimised conditions, the mLAMP-LFD assay showed high specificity. The detection limits of Salmonella spp. and Cronobacter spp. in powdered infant formula (PIF) were as low as 4.3 cfu g −1 and 2.8 cfu g −1, respectively. The whole process can be accomplished in less than 1 h. Moreover, the investigation on 80 PIF samples indicated that the assay performed good feasibility in real samples. Thus, this method could be an effective tool for detecting Salmonella spp. and Cronobacter spp.